2019
DOI: 10.1017/prp.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

A person-centered investigation of math motivation and its correlates to math achievement in elementary students

Abstract: The present study used a person-centered approach to identify math motivation profiles under self-determination theory, and examine whether math achievement varies across different profiles. Data were collected from 2,137 children. Five student motivation profiles were identified: a “high quality” profile characterized by high levels of intrinsic and identified motivation and a low level of controlled motivation, a “high quantity” profile characterized by high levels of these three kinds of motivation, a “low q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
2
9
1
2
Order By: Relevance
“…Murid yang bermotivasi memiliki ketabahan dalaman yang diperlukan untuk belajar dan menyesuaikan diri dengan tuntutan persekitaran pembelajaran (Schumacher & Ifenthaler, 2018;Wigfield et al, 2019). Di samping itu, murid yang mempunyai motivasi yang tinggi lebih berkemungkinan untuk terlibat secara aktif, dan menunjukkan peningkatan prestasi, ketabahan, dan daya cipta dalam pencapaian Matematik (Lv et al, 2019). Dengan ini, pencapaian murid ini masih boleh dipertingkatkan jika motivasi murid ditingkatkan.…”
Section: Pencapaian Muridunclassified
“…Murid yang bermotivasi memiliki ketabahan dalaman yang diperlukan untuk belajar dan menyesuaikan diri dengan tuntutan persekitaran pembelajaran (Schumacher & Ifenthaler, 2018;Wigfield et al, 2019). Di samping itu, murid yang mempunyai motivasi yang tinggi lebih berkemungkinan untuk terlibat secara aktif, dan menunjukkan peningkatan prestasi, ketabahan, dan daya cipta dalam pencapaian Matematik (Lv et al, 2019). Dengan ini, pencapaian murid ini masih boleh dipertingkatkan jika motivasi murid ditingkatkan.…”
Section: Pencapaian Muridunclassified
“…So far, various studies have been conducted to assess elementary and secondary school students' academic motivation profiles. However, some of these studies (Corpus & Wormington, 2014;Hayenga & Corpus, 2010;Oga-Baldwin & Fryer, 2017;Vansteenkiste et al, 2009;Wormington et al, 2012) have only considered the broad categories of autonomous/controlled motivation, while others (Liu et al, 2009;Lv et al, 2019;Oga-Baldwin & Fryer, 2018Paixao & Gamboa, 2017;Ratelle et al, 2007) have relied on a more comprehensive coverage of behavioral regulations. Despite these variations in operationalization, the results tend to converge on four common academic motivation profiles: (a) Autonomous: high autonomous and low controlled; (b) Strongly Motivated: high autonomous and high controlled; (c) Controlled: low autonomous and high controlled; and (d) Non-Motivated: low autonomous and low controlled.…”
Section: Self-determination Theory and Profiles Of Academic Motivationmentioning
confidence: 99%
“…Studies have applied a person-centered approach to the types of motivation of the SDT in a variety of contexts (i.e., education, sport, and work) (11,14,16). In the literature, the nature of these profiles differs from profiles consisting of low to high levels of the more controlled types of motivation 1 in combination with low to high levels of the more autonomous types of motivation (11,13).…”
Section: Literature Overview Motivational Profiles Within Self-determ...mentioning
confidence: 99%
“…However, the contexts of these studies influenced the nature of the profiles that emerged (14,15,17). More specifically, a review of the literature illustrated that studies in the work context reported more truly autonomous profiles than studies in the educational (especially among high school students) and sport (especially among elite athletes) contexts, in which more controlled profiles emerged.…”
Section: Literature Overview Motivational Profiles Within Self-determ...mentioning
confidence: 99%
See 1 more Smart Citation